2023
DOI: 10.3390/ijms242417160
|View full text |Cite
|
Sign up to set email alerts
|

The Structure and Nucleotide-Binding Characteristics of Regulated Cystathionine β-Synthase Domain-Containing Pyrophosphatase without One Catalytic Domain

Ilya M. Zamakhov,
Viktor A. Anashkin,
Andrey V. Moiseenko
et al.

Abstract: Regulatory adenine nucleotide-binding cystathionine β-synthase (CBS) domains are widespread in proteins; however, information on the mechanism of their modulating effects on protein function is scarce. The difficulty in obtaining structural data for such proteins is ascribed to their unusual flexibility and propensity to form higher-order oligomeric structures. In this study, we deleted the most movable domain from the catalytic part of a CBS domain-containing bacterial inorganic pyrophosphatase (CBS-PPase) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Additionally, Zamakhov et al (2023) confirmed the tetrameric nature of these enzymes by purifying and characterizing the enzyme of Desulfobacterium hafniense by transmission electron microscopy and biochemical approaches. They found that a highly flexible region is responsible for limiting the crystallization of these enzymes, which is consistent with the findings of G. intestinalis .…”
Section: Cytoplasmic Ppases Families and Structural Featuresmentioning
confidence: 67%
“…Additionally, Zamakhov et al (2023) confirmed the tetrameric nature of these enzymes by purifying and characterizing the enzyme of Desulfobacterium hafniense by transmission electron microscopy and biochemical approaches. They found that a highly flexible region is responsible for limiting the crystallization of these enzymes, which is consistent with the findings of G. intestinalis .…”
Section: Cytoplasmic Ppases Families and Structural Featuresmentioning
confidence: 67%
“…Unlike the canonical Family II PPases, CBS-PPases form tetramers [ 11 ], which are stabilized by separate crosswise interactions of the catalytic and regulatory parts [ 12 ] ( Figure 1 B). The structure of tetrameric CBS-PPase from Desulfitobacterium hafniense ( dh PPase) without the DHHA2 domain was obtained at 16 Å resolution by single-particle electron microscopy [ 12 ], whereas the structures of the dimeric regulatory part of homologous Clostridium perfringens CBS-PPase ( cp PPase) in complexes with AMP (inhibitor) and Ap 4 A (activator) were determined at 2.3 Å by X-ray crystallography [ 13 ]. Although each CBS domain can bind a mono-adenosine phosphate and there are two CBS domains per subunit, the structures indicated the binding stoichiometry of one molecule of AMP per subunit or one molecule of Ap 4 A per dimer [ 10 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“… ( A ) Domain composition of canonical PPase and CBS-PPase of Family II. ( B ) 3D structure of tetrameric dh PPase without the DHHA2 domain suggested by low-resolution cryo-EM and molecular modeling [ 12 ]. The four subunits, a1–a4, are shown in different colors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation